Changes of corneal biomechanical and biometrical properties after combined phacoemulsification with viscocanalostomy surgery in patients with open-angle glaucoma - Ali Azimi; Elham Sadeghi; Hamidreza Hassanipour; Pardis Bostanian; Alireza Attar; Dorna Eghtedari; Zahra Sharafi; Hooman Razmi; Rajesh S Kumar; Ian Conner (BMC Ophthalmology)
Abstract Purpose To assess corneal biomechanical changes after phacoemulsification and ab-externo viscocanalostomy (phaco-visco) surgery in patients with open-angle glaucoma (OAG). Methods Patients with OAG and cataract, visual acuity < 20/40 Snellen, were included. Pre- and postoperative evaluations were performed. Keratometric and aberrometry assessments were done with Oculus Pentacam AXL, and corneal biomechanics were evaluated using Corvis ST. Wilcoxon signed-rank and Chi-square tests were used. Results This study included 30 eyes from 28 patients with OAG who underwent phaco-visco surgery. The mean age was 67.57 ± 9.20 years, with 50% being male. The mean postoperative follow-up duration was 4.1 ± 2.1 months. Postoperatively, biomechanically corrected intraocular pressure (bIOP) significantly decreased (-1.8 ± 4.7, P = 0.008), while central corneal thickness (CCT) showed no significant change (+ 0.333 ± 9.536, P = 0.810). Significant increases were observed in deflection amplitude max (+ 0.841 ± 0.173, P = 0.002), peak distance (+ 0.242 ± 0.458, P = 0.001), front astigmatism (+ 0.210 ± 0.420, P = 0.013), index of height asymmetry (+ 3.146 ± 6.374, P = 0.015), and index of height deviation (+ 0.007 ± 0.010, P = 0.001). Additionally, anterior chamber (AC) parameters such as AC depth (P = 0.001) and AC volume (P < 0.001) significantly increased following surgery. Conclusions This study shows that phaco-visco surgery in OAG eyes may increase corneal softening, decrease bIOP without altering CCT, induce corneal front astigmatism, and cause AC parameters changes. Corvis ST helps for more accurate IOP assessment and toric IOL planning.